2020
DOI: 10.3390/mi11121104
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Laser Assisted Diamond Turning of Binderless Tungsten Carbide by In-Process Heating

Abstract: Binderless tungsten carbide (WC) finds widespread applications in precision glass molding (PGM). Grinding and polishing are the main processes to realize optical surface finish on binderless WC mold inserts. The laser assisted turning (LAT) by in-process heating is an efficient method to enhance the machinability of hard and brittle materials. In this paper, laser heating temperature was pre-calculated by the finite element analysis, and was utilized to facilitate laser power selection. The effects of rake ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…After laser-assisted machining, the surface machining marks are significantly reduced, no pits and micro-cracks. Due to the lack of precision of ordinary CNC lathe, the surface roughness of the workpiece after processing is higher than the experimental results of You et al [13]. However, it can be seen that the surface quality can still be improved by in-situ LAT on an ordinary CNC lathe.…”
Section: Machining Surface By In-situ Latmentioning
confidence: 70%
See 1 more Smart Citation
“…After laser-assisted machining, the surface machining marks are significantly reduced, no pits and micro-cracks. Due to the lack of precision of ordinary CNC lathe, the surface roughness of the workpiece after processing is higher than the experimental results of You et al [13]. However, it can be seen that the surface quality can still be improved by in-situ LAT on an ordinary CNC lathe.…”
Section: Machining Surface By In-situ Latmentioning
confidence: 70%
“…The results showed that the surface quality was improved and the tool life was significantly improved with the laser assisted. You et al [13,14] studied in-situ LAT of binderless tungsten carbide through experiments and finite element simulation. They found that the optimal power for LAT binderless tungsten carbide ranges from 10W to 15W.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, You and Fang et al proposed to use LASER machining when machining the cutting edges of PCD tools. This machining method does not cause mechanical wear, which is an innovative alternative for manufacturing and machining tools made of PCD material [22].…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue showcases 12 state-of-the-art examples of modeling and simulation in micro- and nano-manufacturing processes. The papers that are published in this Special Issue explore the following micro- and nano-manufacturing processes: laser texturing [ 1 , 2 ], 3D printing [ 3 , 4 ], grinding [ 5 , 6 ], turning [ 7 , 8 ], and electrochemical machining [ 9 , 10 ]. The remaining papers cover lithography-based manufacturing [ 11 ], and micro- and nano-scale design aspects [ 12 ].…”
mentioning
confidence: 99%
“…Elastic-plastic deformation and ploughing were observed when the feed rate was lower than the cutting edge radius. You et al carried out an experimental investigation, focusing on laser-assisted turning by the in-process heating of tungsten carbide, for precision glass molding [ 8 ]. The process guides the laser beam passes through the transparent tool, to heat the material locally, thereby decreasing the ultra-high tungsten carbide hardness and altering the fracture toughness as soon as the tool interacts with the material.…”
mentioning
confidence: 99%